A Prospective Observational Study on Maternal and Perinatal Outcome in Trial of Labour after Caesarean at Tertiary Care Hospital, India - Prabhakarrao, Ingle Sharad; Bansode, Shalaka; Balakuduru, Sumathi (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Background: The purpose of this study was to compare maternal and perinatal outcomes in a trial of labour after caesarean (TOLAC) and an emergency repeat caesarean delivery (ERCD). Design: A one-year prospective observational study at a tertiary care centre. Methods: Selection of candidates for Vaginal Birth after caesarean section (VBAC) was based on the 2010 American College of Obstetricians and Gynecologists’ (ACOG) recommendation. The maternal outcome was measured using the VBAC success rate, maternal complications, and the number of days spent in the hospital. The perinatal outcome was measured using the 5 minute Apgar score and the need for neonatal intensive care unit (NICU) admission. Results: Vaginal delivery was trialled on 250 patients. The success rate for VBAC was 169/249. (67.9 percent). Repeat CS was required for 80/249 (32.1%) of the patients. Cases with a Bishop score greater than 6 had a higher rate of vaginal delivery (89.6%) than cases with a Bishop score \(\le\)6 (17.4 %) (p=0.01). Spontaneous labour had better VBAC success rate (91.8%) than induced labour (55.5%) (p=<0.01). 8/12 (66.6%) subjects with history of previous vaginal deliveries delivered vaginally. In comparison to 3/80 from repeat CS, 5/169 VBAC babies had a poor 5-minute Apgar score. Conclusions: VBAC has the advantages of a shorter hospital stay, less morbidity, and lower costs. Given that foetal morbidity and mortality from TOL are comparable to that of women labouring without a scar, TOL may be encouraged. Women can be given TOL with careful monitoring and taken for emergency LSCS on minimal indication, and this may be the best solution to managing a previous CS in labour.